Adaptive control of dynamic plant in the presence of irregular disturbances based on methods for current functional identification its model in off-line and on-line modes - Азарсков, В.М.; Житецький, Л.С.; Сущенко, О.А. (Proceedings of National Aviation University (archive), 2005)
The two types of adaptive control systems containing an identifier in feedback circuit are considered. In contrast to the system of the first type, in which the on-line current estimation of unknown plant parameters is implemented, the off-line mode is introduced in the systems of the second type at an initial stage of adaptation. Some features of these types of systems are established. Their comparative evaluation is given.